Setting Refund and Warranty Clauses Urgency in Electronic Agreements: Harmonization between Covenant Law & Consumer Protection - Abdul Fatakh (JURNAL AKTA, 2025)
The rapid growth of electronic transactions in the digital era has driven the transformation of conventional contract models into e-contracts based on digital and automated systems. However, this transformation poses serious challenges in terms of legal protection for consumers, particularly regarding refund and warranty clauses, which are often unilaterally drafted by businesses. The main issue addressed in this research is the lack of clarity in the substance of refund and product warranty clauses in electronic contracts, which contradicts the principles of contractual fairness and consumer protection. This study used a normative juridical method with statutory and comparative legal approaches, focusing on international practices, particularly in the European Union. The findings reveal a regulatory gap in Indonesia's positive law, including Law No. 8 of 1999 on Consumer Protection, Law No. 11 of 2008 on Electronic Information and Transactions, and the Indonesian Civil Code. The absence of minimum standards for refund and warranty clauses results in an imbalance of power between businesses and consumers and undermines legal certainty in digital transactions. Therefore, there is a need to harmonize the principle of freedom of contract with consumer protection through the establishment of regulations that govern standard clauses in a transparent, proportional, and fair manner. Such regulation is expected to resolve the dilemma between business efficiency and the fairness of legal protection, and to foster the development of a sustainable digital trade ecosystem.